Bent Tibial Nail with Refracture: A Cost-Effective Removal Method. Issue 2 (April 2020) - Pathak, Subodh Kumar; Gautam, Rakesh Kumar; Anjum, Rashid; Sharma, Aryan
Abstract : Case: A 45-year old man presented with a right open tibial fracture with a prominent, fixed deformity because of a retained right tibial intramedullary nail from a previous tibial fracture. After multiple futile intraoperative attempts to extract the bent nail, it was finally sectioned using an industrial drill bit that permitted its removal and revision tibial nailing. Conclusions: A tibial fracture resulting in a retained, bent nail presents unique challenges for nail extraction and subsequent exchange nailing. Failed implant removal can be limited by the equipment available in the operating theater. In this setting, the judicious use of inexpensive industrial materials and instruments may be effective in select cases.